Analisis Pengaruh Net Profit Margin (Npm), Return OnAsset (Roa), Dan Return On Equity (Roe) TerhadapHarga Saham Pada Perusahaan Makanan DanMinuman Yang Terdaftar Di Bei - Pratiwi, Dias, Drs. Ma'ruf, MM (2017)
This study aimed to analyze the influence of net profit margin, return on assets, and return on equity on stock price on Food and Beverage listed in Indonesia Stock Exchange 2011-2015 period. The population in this study is the Food and Drink 2011-2015. Mechanical sample selection using purposive sampling that the sample selection technique based on certain characteristics. Data obtained by the publication of Indonesia Stock Exchange (IDX) 2011-2015. The number of samples that meet the criteria of a total of 14 companies to obtain the data 70 data and processed into 63 data. The method of analysis used in this study with multiple linear regression analysis, F test and t test. The findings indicate that simultaneous ROE, ROA and NPM significant effect on stock prices. Partially ROE have significant effect on stock prices, while NPM and ROA no significant effect on stock prices. On the ROE, ROA and NPM is able to explain the share price of 35,7% and the remaining 64,3%. Keywords : Return On Equity, Return On Asset, Net Profit Margin, Stock Price